The Effect of Human Resources Quality and Regional Financial Accounting System on the Quality of Local Government Financial Statements Moderated by Organizational Commitment - Anwar, Anwar; Haliah, Haliah; Nirwana, Nirwana; Kusumawati, Andi Kusumawati (Cita konsultindo, 2025)
This study aims to examine the effect of human resource quality and regional financial accounting systems on the quality of local government financial statements moderated by organizational commitment. The research approach uses a quantitative approach in the form of survey research. The sampling technique used quota sampling, so that 180 employees were obtained as research respondents. The results showed that the quality of human resources had no effect on the quality of financial statements, the regional financial accounting system had a positive and significant effect on financial statements, organizational commitment was unable to moderate the relationship between the quality of human resources on the quality of financial statements and organizational commitment was unable to moderate the relationship between the regional financial accounting system on the quality of financial statements.